Method for evaluating wear resistance of rubber composition, and rubber composition

The mass fractal dimension D of the rubber composition was obtained by X-ray or neutron scattering measurement and curve fitting, and the problem of inaccurate evaluation of wear resistance of rubber compositions in the prior art was solved, and high precision, rapid, Economic evaluation method.

CN119438263APending Publication Date: 2025-02-14SUMITOMO RUBBER INDUSTRIES LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410944918.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-04-15
Filing Date
2024-07-15
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

In the prior art, when evaluating the wear resistance of tire tread rubber, differences in vulcanization conditions lead to inconsistent prediction results with actual driving performance.

Method used

The scattering intensity curve of the rubber composition is obtained by X-ray scattering measurement or neutron scattering measurement, and the mass fractal dimension D is obtained by a specific curve fitting formula to evaluate the wear resistance of the rubber composition with high accuracy.

Benefits of technology

A high-precision evaluation of the wear resistance of the rubber composition is achieved, and the actual driving performance of the rubber composition can be predicted in a short time and at low cost, avoiding the problem of predictions in the prior art that are inconsistent with the actual situation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119438263A_ABST
    Figure CN119438263A_ABST
Patent Text Reader

Abstract

Provided is a method for evaluating the wear resistance of a rubber composition with high accuracy. The present invention relates to a method for evaluating the wear resistance of a rubber composition by means of X-ray scattering measurement or neutron scattering measurement, said method being a method for evaluating the wear resistance of a rubber composition on the basis of a mass fractal dimension D, the mass fractal dimension D is obtained by curve-fitting a scattering intensity curve I (q), which is obtained by performing X-ray scattering measurement or neutron scattering measurement in a q region represented by formula (1), by formula (2). [Number 1] (Formula 1) # imgabs0 # [theta] is the scattering angle, and [lambda] is the wavelength of an X-ray or a neutron ray. [Number 2] (Formula 2) I (q) < q-DD: mass fractal dimension.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a method for evaluating the wear resistance of a rubber composition and the rubber composition. Background Art

[0002] Conventionally, as a method for evaluating the wear resistance of a tire, there is a known method of producing a vulcanized rubber for a wear test using the same formulation as the tire tread rubber, subjecting the vulcanized rubber to wear in an indoor wear tester such as a Lamborn abrasion tester, and performing the evaluation (see Patent Document 1).

[0003] However, in the conventional methods, the properties of the vulcanized rubber used for the wear test and the tread rubber of the tire to be evaluated may be different due to differences in vulcanization conditions, etc. Therefore, there is a problem that the wear resistance result predicted by the conventional evaluation method is inconsistent with the wear resistance result when the tire to be evaluated is actually mounted on a vehicle and driven. [Prior art literature] [Patent Literature]

[0004] [Patent Document 1] Japanese Patent Application Publication No. 2005-308447 Summary of the invention [Problems to be solved by the invention]

[0005] An object of the present invention is to solve the above-mentioned problems and to provide a method for evaluating the wear resistance of a rubber composition with high accuracy.

Methods to solve the problem

[0006] The present inventors have found that the mass fractal dimension D obtained by curve fitting a scattering intensity curve obtained by performing X-ray scattering measurement or neutron scattering measurement in a specific region using a specific formula shows a high correlation with the wear resistance of the rubber composition, and the smaller the mass fractal dimension D, the better the wear resistance tends to be. It is speculated that since the filler network is not overdeveloped (i.e., the mass fractal dimension is small), the number of microscopic sacrificial fractures increases, thereby suppressing macroscopic fractures (i.e., wear), and improving wear resistance.

[0007] That is, the present invention relates to a method characterized in that it is a method for evaluating the wear resistance of a rubber composition by X-ray scattering measurement or neutron scattering measurement. Based on the scattering intensity curve I obtained by performing X-ray scattering measurement or neutron scattering measurement in the q region represented by the following (Formula 1), (q) The wear resistance of the rubber composition was evaluated by using the mass fractal dimension D obtained by curve fitting using the following (Formula 2).

Number 1

Number 2

[0008] The present invention is a method for evaluating the wear resistance of a rubber composition by X-ray scattering measurement or neutron scattering measurement, and is based on a scattering intensity curve I obtained by performing X-ray scattering measurement or neutron scattering measurement in the q region represented by the above (Formula 1). (q) , the method of evaluating the wear resistance of the rubber composition by using the mass fractal dimension D obtained by fitting the curve of (Formula 2) can evaluate the wear resistance of the rubber composition with high accuracy. That is, the evaluation method based on the wear resistance of the actual vehicle requires the manufacture of tires and the implementation of driving tests, which is time-consuming and cost-intensive. On the other hand, in the method of the present invention, the wear resistance can be evaluated in a short time, at low cost, and with high accuracy by a simple method of manufacturing a rubber test piece (rubber composition) and irradiating X-rays or neutrons. BRIEF DESCRIPTION OF THE DRAWINGS

[0009]

Figure 1

[0010] The present invention is a method for evaluating the wear resistance of a rubber composition by X-ray scattering measurement or neutron scattering measurement, based on a scattering intensity curve I obtained by performing X-ray scattering measurement or neutron scattering measurement in the q region represented by the above (Formula 1). (q) , a method for evaluating the wear resistance of a rubber composition using the mass fractal dimension D obtained by curve fitting of (Formula 2).

[0011] In the above method, as the X-ray scattering measurement, SAXS (Small-Angle X-ray Scattering, small-angle X-ray scattering (scattering angle: usually 10 degrees or less)) measurement can be preferably used, which is a measurement in which the rubber composition is irradiated with X-rays to measure the scattering intensity. In addition, in small-angle X-ray scattering, by measuring X-rays with a small scattering angle among X-rays scattered by irradiating X-rays on a substance, structural information of the substance can be obtained, and an ordered structure at a level of several nanometers, such as a microscopic phase separation structure of a polymer material, can be analyzed.

[0012] In order to obtain detailed molecular structure information by SAXS measurement, it is desirable to be able to measure an X-ray scattering spectrum with a high S / N ratio. Therefore, the X-rays emitted by a synchrotron preferably have a wavelength of at least 10 10 (photons / s / mrad 2 / mm 2 / 0.1%bw) or more. In addition, bw represents the band width of X-rays emitted from the synchrotron. Examples of such synchrotrons include beam lines BL03XU and BL20XU of SPring-8, a large-scale radiation facility owned by the High Brightness Light Science Research Foundation.

[0013] The brightness of the above X-rays (photons / s / mrad 2 / mm 2 / 0.1% bw) preferably 10 10 More than 10 12 The upper limit is not particularly limited, but it is preferable to use an X-ray intensity that is not more than the level at which there is no radiation damage.

[0014] In addition, the photon number (photons / s) of the above X-rays is preferably 10 7 More than 10 9 The upper limit is not particularly limited, but it is preferable to use an X-ray intensity that is not more than the level at which there is no radiation damage.

[0015] In the above method, as the neutron scattering measurement, SANS (Small-Angle Neutron Scattering) measurement can be preferably used, which is a measurement in which neutron rays are irradiated to the rubber composition and the scattering intensity is measured. In addition, by small-angle neutron scattering, neutron rays with a small scattering angle can be measured among neutron rays scattered by irradiating neutron rays to a substance, thereby obtaining structural information of the substance, and analyzing ordered structures at the level of several nanometers, such as microscopic phase separation structures of polymer materials.

[0016] The SANS measurement can be performed using a known method using a magnetic structure or a deuterated method. When the deuterated method is used, for example, a polymer material can be swelled by a deuterated solvent, and a neutron beam can be irradiated onto the polymer material in equilibrium in the deuterated solvent to measure the scattering intensity. Here, examples of the deuterated solvent for swelling the polymer material include heavy water, deuterated hexane, deuterated toluene, deuterated chloroform, deuterated methanol, and deuterated DMSO ((D 3 C) 2 S=O), deuterated tetrahydrofuran, deuterated acetonitrile, deuterated dichloromethane, deuterated benzene, deuterated N,N-dimethylformamide, etc.

[0017] Neutron rays used in neutron scattering measurements such as SANS can be obtained using beam line SANS-J of the JRR-3 research reactor owned by the Japan Atomic Energy Agency, an independent administrative institution.

[0018] As with SAXS measurement, the neutron beam intensity (neutrons / cm 2 / s) is preferably 10 3 More than 10 4 The upper limit is not particularly limited, but it is preferable to use a neutron beam intensity that is not more than the level at which there is no radiation damage.

[0019] In the above method, the X-ray and neutron scattering measurements are performed in the q region represented by the following (Formula 1). -1 ) area, the larger the value, the more subtle the molecular structure information can be obtained. Therefore, it is preferred that q is 10nm for X-ray and neutron scattering measurements. -1 The area below, more preferably 5×10 -2 nm -1 The following region is particularly preferred, 2×10 -3 nm -1 Above, 5×10 - 3 nm -1 The following area.

Number 3

[0020] In the SAXS measurement, scattered X-rays are detected by an X-ray detection device, and an image is generated by an image processing device or the like using X-ray detection data from the X-ray detection device.

[0021] As the X-ray detection device, for example, a two-dimensional detector (X-ray film, nuclear plate, X-ray camera tube, X-ray fluorescence multiplier tube, X-ray image intensifier, X-ray imaging plate, X-ray CCD, X-ray amorphous, etc.), a line sensor, or a one-dimensional detector can be used. The X-ray detection device can be appropriately selected according to the type and state of the polymer material to be analyzed.

[0022] As the image processing device, a device capable of generating a general X-ray scattered image based on X-ray detection data obtained by an X-ray detection device can be appropriately used.

[0023] Even in SANS measurement, it is possible to measure based on the same principle as SAXS measurement, by detecting scattered neutron rays by a neutron ray detection device, and using neutron ray detection data from the neutron ray detection device, generating an image by an image processing device, etc. Here, as in the above, a known two-dimensional detector or a one-dimensional detector can be used as the neutron ray detection device, and a known device capable of generating a neutron ray scattered image can be used as the image processing device, and they can be appropriately selected.

[0024] At the same time, the mass fractal dimension D can be obtained by performing SAXS measurement, SANS measurement or the like on the rubber composition and analyzing the obtained scattering intensity curve by the following method.

[0025] like Figure 1 As shown, for the scattering intensity curve I obtained by SAXS measurement and SANS measurement (q) , using the following (Formula 2) for curve fitting, the mass fractal dimension D as a fitting parameter can be obtained by the least squares method.

Number 4

[0026] The mass fractal dimension D obtained by fitting is, for example, a molecular structure containing at least one reinforcing agent such as carbon black, silica, and / or a molecular structure having the general formula mM·xSiOy·zH 2 In the case of a rubber composition containing an inorganic filler represented by O (M is a metal selected from aluminum, magnesium, titanium, calcium and zirconium, oxides and hydrates of these metals, hydrates thereof and carbonates of these metals, and m, x, y and z are constants), it can be presumed that the reinforcing agent and / or the inorganic filler are derived.

[0027] Moreover, as described above, the mass fractal dimension D has a high correlation with wear resistance, and the smaller the value of D, the better the wear resistance. In particular, if the rubber composition has D less than 2.30, it can have excellent wear resistance. As the value of D, it is preferably 2.25 or less, more preferably 2.20 or less, further preferably 2.17 or less, further preferably 2.15 or less, and further preferably 2.12 or less. On the other hand, as the lower limit of the value of D, since it is 1≦D≦3 in principle, it is 1.00.

[0028] Here, in the present invention, the mass fractal dimension D refers to the packing state of a substance per unit volume, and in a rubber composition filled with fillers, it refers to the packing state of the filler (filler) per unit volume, that is, it is estimated to be the development state of the filler network.

[0029] It is considered that when the filler network is not excessively developed (ie, when the mass fractal dimension D is small), the number of microscopic sacrificial fractures increases, thereby suppressing macroscopic fractures (ie, wear).

[0030] The mass fractal dimension D can be adjusted by the type and amount of chemical agents such as rubber components, fillers, or silane coupling agents mixed in the rubber composition. The mass fractal dimension D can be reduced by changing the dispersibility of silica according to the type of silane coupling agent. Specifically, the mass fractal dimension D can be reduced by using the modified rubber described below as the rubber component, reducing the amount of the modified rubber mixed, and using a mercapto-based silane coupling agent as the silane coupling agent.

[0031] As the rubber composition (rubber material) suitable for use in the method of the present invention, for example, a material containing a rubber component and a filler can be preferably used.

[0032] The weight average molecular weight of the rubber component that can be used in the above-mentioned rubber composition is preferably 50,000 or more, more preferably 150,000 or more, further preferably 200,000 or more, and particularly preferably 270,000 or more, and is preferably 2,000,000 or less, more preferably 1,500,000 or less, and further preferably 1,000,000 or less.

[0033] In addition, in this specification, the weight average molecular weight (Mw) and the number average molecular weight (Mn) can be obtained by converting the measured values ​​based on gel permeation chromatography (GPC) (GPC-8000 series manufactured by Tosoh Corporation, detector: differential refractometer, column: TSKGEL SUPERMULTIPORE HZ-M manufactured by Tosoh Corporation) into standard polystyrene.

[0034] The rubber component that can be used in the above-mentioned rubber composition can be a non-modified rubber or a modified rubber. From the viewpoint of reducing the mass fractal dimension D of the rubber composition, a modified rubber is preferred. As a modified rubber, a rubber having a functional group that interacts with a filler such as silica can be cited. For example, a terminal modified rubber (a terminal modified rubber having the above-mentioned functional group at the end) in which at least one end of the rubber is modified with a compound (modifier) ​​having the above-mentioned functional group, a main chain modified rubber having the above-mentioned functional group on the main chain, a main chain terminal modified rubber having the above-mentioned functional group on the main chain and the end (for example, a main chain terminal modified rubber having the above-mentioned functional group on the main chain and at least one end modified with the above-mentioned modifier), a terminal modified rubber having a hydroxyl group or an epoxy group introduced by modification (coupling) of a multifunctional compound having two or more epoxy groups in the molecule, and the like can be cited.

[0035] As the above functional group, for example, amino, amide, silyl, alkoxysilyl, isocyanate, imino, imidazolyl, urea, ether, carbonyl, oxycarbonyl, mercapto, thioether, disulfide, sulfonyl, sulfinyl, thiocarbonyl, ammonium, imino, hydrazine, azo, diazo, carboxyl, nitrile, pyridyl, alkoxy, hydroxyl, oxy, epoxy, etc. can be listed. In addition, these functional groups may also have a substituent. Among them, amino (preferably an amino group in which the hydrogen atom of the amino group is substituted by an alkyl group having 1 to 6 carbon atoms), alkoxy (preferably an alkoxy group having 1 to 6 carbon atoms), alkoxysilyl (preferably an alkoxysilyl group having 1 to 6 carbon atoms) are preferred.

[0036] As the rubber component that can be used in the above-mentioned rubber composition, specifically, diene rubber etc. can be cited. As diene rubber, isoprene rubber, butadiene rubber (BR), styrene butadiene rubber (SBR), styrene isoprene butadiene rubber (SIBR), ethylene propylene diene rubber (EPDM), chloroprene rubber (CR), acrylonitrile-butadiene rubber (NBR) etc. can be cited. In addition, as rubber component, butyl rubber, fluororubber etc. can also be cited. These can be used alone, or more than two kinds can be used in combination. In addition, these rubber components can also be modified, hydrogenated, and can also use the volume-increasing rubber increased by oil, resin, liquid rubber component etc. Wherein, from the viewpoint of reducing the mass fractal dimension D of the rubber composition, the above-mentioned rubber composition is preferably containing diene rubber, more preferably containing at least one selected from isoprene rubber, BR and SBR, more preferably containing SBR, and more preferably containing BR and SBR.

[0037] In addition, as the above-mentioned modified rubber, specifically, the following "a polymer in which a conjugated diene compound and / or an aromatic vinyl compound is copolymerized with a nitrogen-containing compound represented by the following general formula, and further, at least one end is modified with a modifier having a functional group containing at least one or more atoms selected from nitrogen, oxygen, and silicon" described in Japanese Patent Application Publication No. 2010-116554 can be cited.

Chemistry 1

Chemistry 2

Chemistry 3

Chemistry 4

Chemistry 5

[0038] When the rubber composition contains isoprene rubber, the content of the isoprene rubber in 100% by mass of the rubber component is preferably 5% by mass or more, more preferably 10% by mass or more, and is preferably 30% by mass or less, more preferably 20% by mass or less.

[0039] When the rubber composition contains BR, the content of BR in 100% by mass of the rubber component is preferably 5% by mass or more, more preferably 15% by mass or more, further preferably 20% by mass or more, and even more preferably 30% by mass or more, and is preferably 60% by mass or less, and more preferably 40% by mass or less, from the viewpoint of reducing the mass fractal dimension D of the rubber composition.

[0040] When the rubber composition contains SBR, from the viewpoint of reducing the mass fractal dimension D of the rubber composition, the content of SBR in 100 mass% of the rubber component is preferably 40 mass% or more, more preferably 60 mass% or more, and is preferably 95 mass% or less, more preferably 85 mass% or less, further preferably 80 mass% or less, and further preferably 70 mass% or less.

[0041] As fillers that can be used in the rubber composition, carbon atom fillers, inorganic fillers, etc. can be cited. As carbon atom fillers, carbon black can be used, and as inorganic fillers, silicon dioxide, metal salts of sulfuric acid, silicon carbide, compounds represented by the following formulas, etc. can be used. mM·xSiOy·zH 2 O (In the formula, M is at least one metal selected from Al, Mg, Ti, Ca and Zr, an oxide or hydroxide of the metal, m is an integer of 1 to 5, x is an integer of 0 to 10, y is an integer of 2 to 5, and z is an integer of 0 to 10.) Examples of the compound represented by the above formula include alumina, alumina hydrate, aluminum hydroxide, magnesium hydroxide, talc, titanium white, titanium black, calcium oxide, calcium hydroxide, calcium aluminum oxide, clay, pyrophyllite, bentonite, aluminum silicate, calcium silicate, calcium aluminum silicate, magnesium silicate, zirconium, and zirconium oxide.

[0042] These fillers may be used alone or in combination of two or more. Among them, the rubber composition preferably contains carbon black and / or silica, and more preferably contains silica.

[0043] As carbon black, there is no particular limitation, and examples thereof include N134, N110, N220, N234, N219, N339, N330, N326, N351, N550, and N762. As commercially available products, products of Asahi Carbon Co., Ltd., Cabot Co., Ltd., Tokai Carbon Co., Ltd., Mitsubishi Chemical Co., Ltd., Lion Co., Ltd., Shin Nichika Carbon Co., Ltd., and Columbia Carbon Co., Ltd. can be used. These can be used alone or in combination of two or more.

[0044] Nitrogen adsorption specific surface area of ​​carbon black (N 2 SA) is preferably 75m 2 / g or more, more preferably 95m 2 / g or more, preferably 120 m 2 / g or less, more preferably 100m / g 2 When it is within the above range, a better effect tends to be obtained. In addition, the N 2 SA is a value measured in accordance with JIS K6217-2:2001.

[0045] When the rubber composition contains carbon black, the content of carbon black is preferably 1 part by mass or more, more preferably 3 parts by mass or more, relative to 100 parts by mass of the rubber component, from the viewpoint of reducing the mass fractal dimension D of the rubber composition. In addition, it is preferably 20 parts by mass or less, more preferably 10 parts by mass or less.

[0046] As silicon dioxide, for example, dry process silicon dioxide (anhydrous silicic acid), wet process silicon dioxide (hydrous silicic acid) etc. can be listed. For the reason that there are more silanol groups, wet process silicon dioxide is preferred. As commercially available products, products of Evonik Degussa, Tosoh Silica Chemical Co., Ltd., Solvay Japan Co., Ltd., Tokuyama Co., Ltd. etc. can be used. These can be used alone or in combination of two or more.

[0047] The nitrogen adsorption specific surface area of ​​silicon dioxide (N 2 SA) is preferably 50m 2 / g or more, more preferably 100m 2 / g or more, preferably 250 m 2 / g or less, more preferably 220m 2 / g or less. When it is within the above range, a better effect tends to be obtained. 2 SA is a value measured by the BET method according to ASTM D3037-81.

[0048] When the rubber composition contains silica, the content of silica is preferably 30 parts by mass or more, more preferably 60 parts by mass or more, and is preferably 120 parts by mass or less, more preferably 100 parts by mass or less, relative to 100 parts by mass of the rubber component, from the viewpoint of reducing the mass fractal dimension D of the rubber composition.

[0049] In the rubber composition, the content of the filler (the total amount of carbon atom-based fillers such as carbon black, silica, metal salts of sulfuric acid, silicon carbide, inorganic fillers such as the compound represented by the above formula) is preferably 30 parts by mass or more, more preferably 60 parts by mass or more, and is preferably 120 parts by mass or less, more preferably 100 parts by mass or less, relative to 100 parts by mass of the rubber component.

[0050] When the rubber composition contains silica, it preferably further contains a silane coupling agent. The silane coupling agent is not particularly limited, and examples thereof include bis(3-triethoxysilylpropyl)tetrasulfide, bis(2-triethoxysilylethyl)tetrasulfide, bis(4-triethoxysilylbutyl)tetrasulfide, bis(3-trimethoxysilylpropyl)tetrasulfide, bis(2-trimethoxysilylethyl)tetrasulfide, bis(2-triethoxysilylethyl)trisulfide, bis(4-trimethoxysilylbutyl)tetrasulfide, bis(3-triethoxysilylpropyl) disulfide, bis(2-triethoxysilylethyl) disulfide, bis(4-triethoxysilylbutyl) disulfide, bis(3-trimethoxysilylpropyl) disulfide, bis(2-trimethoxysilylethyl) disulfide, bis(4-trimethoxysilylbutyl) disulfide, 3-trimethoxysilylpropyl-N,N-dimethylthiocarbamoyl Sulfide-based silanes such as trimethoxysilyl tetrasulfide, 2-triethoxysilylethyl-N,N-dimethylthiocarbamoyl tetrasulfide, and 3-triethoxysilylpropyl methacrylate monosulfide; mercapto-based silanes such as 3-mercaptopropyltrimethoxysilane, 2-mercaptoethyltriethoxysilane, and NXT and NXT-Z manufactured by Momentive; vinyl-based silanes such as vinyltriethoxysilane and vinyltrimethoxysilane; 3-aminopropyltriethoxysilane; Silane, 3-aminopropyltrimethoxysilane and other amino series, γ-glycidoxypropyltriethoxysilane, γ-glycidoxypropyltrimethoxysilane and other glycidoxy series, 3-nitropropyltrimethoxysilane, 3-nitropropyltriethoxysilane and other nitro series, 3-chloropropyltrimethoxysilane, 3-chloropropyltriethoxysilane and other chlorine series, etc., among which, from the viewpoint of reducing the mass fractal dimension D of the rubber composition, mercapto-based silane coupling agents are preferred. As commercially available products, products of EVONIK, Momentive, Shin-Etsu Silicone Co., Ltd., Tokyo Chemical Industry Co., Ltd., Azmax Co., Ltd., Toray Dow Corning Co., Ltd., etc. can be used. These can be used alone or in combination of two or more.

[0051] The content of the silane coupling agent is preferably 1 part by mass or more, more preferably 3 parts by mass or more, and further preferably 4 parts by mass or more, and is preferably 10 parts by mass or less, and more preferably 7 parts by mass or less, per 100 parts by mass of silica.

[0052] The rubber composition may contain sulfur. Examples of sulfur include powdered sulfur, precipitated sulfur, colloidal sulfur, insoluble sulfur, highly dispersible sulfur, and soluble sulfur commonly used in the rubber industry.

[0053] In the rubber composition, the sulfur content is preferably 1.0 parts by mass or more, more preferably 1.3 parts by mass or more, and preferably 7.0 parts by mass or less, more preferably 5.0 parts by mass or less, per 100 parts by mass of the rubber component.

[0054] The rubber composition may contain a vulcanization accelerator. Examples of the vulcanization accelerator include thiazole-based vulcanization accelerators such as 2-mercaptobenzothiazole, di-2-benzothiazolyl disulfide, and N-cyclohexyl-2-benzothiazolyl sulfenamide; thiuram-based vulcanization accelerators such as tetramethylthiuram disulfide (TMTD), tetrabenzylthiuram disulfide (TBzTD), and tetrakis(2-ethylhexyl)thiuram disulfide (TOT-N); sulfenamide-based vulcanization accelerators such as N-cyclohexyl-2-benzothiazole sulfenamide, N-tert-butyl-2-benzothiazole sulfenamide, N-oxyethylene-2-benzothiazole sulfenamide, and N,N'-diisopropyl-2-benzothiazole sulfenamide; and guanidine-based vulcanization accelerators such as diphenylguanidine, di-o-tolylguanidine, and o-tolylbiguanide. These may be used alone or in combination of two or more.

[0055] In the rubber composition, the content of the vulcanization accelerator is preferably 0.5 parts by mass or more, more preferably 1.0 parts by mass or more, per 100 parts by mass of the rubber component, and the upper limit is preferably 8.0 parts by mass or less, more preferably 6.0 parts by mass or less.

[0056] The rubber composition may contain other compounding agents such as a plasticizer (oil, liquid polymer, resin, etc.), an antioxidant, stearic acid, zinc oxide, wax, and a mold release agent.

[0057] The rubber composition (rubber material) can be produced, for example, by kneading the above-mentioned components using a rubber kneading device such as an open roll mill or a Banbury mixer, followed by vulcanization.

[0058] The kneading conditions may be appropriately known conditions. For example, as a kneading condition, in the basic kneading process of kneading additives other than the vulcanizing agent (cross-linking agent) and the vulcanization accelerator, the kneading temperature is preferably above 100°C, more preferably above 120°C, and preferably below 180°C, and more preferably below 170°C. In the final kneading process of kneading the vulcanizing agent and the vulcanization accelerator, the kneading temperature is preferably above 80°C, and preferably below 120°C, and more preferably below 110°C. In addition, a vulcanization treatment such as press vulcanization is usually applied to the composition mixed with the vulcanizing agent and the vulcanization accelerator. As the vulcanization temperature, it is preferably above 140°C, more preferably above 150°C, and preferably below 190°C, and more preferably below 185°C.

[0059] The method of the present invention can be preferably used to evaluate the wear resistance of tire components such as treads because it can evaluate the wear resistance with high accuracy. When the rubber composition is used to manufacture a pneumatic tire, the rubber composition is extruded in an unvulcanized stage in the shape of a tread, etc., and formed in a tire molding machine by a conventional method, and bonded together with other tire components to form an unvulcanized tire (green tire), and then heated and pressurized in a vulcanizing device. [Example]

[0060] The present invention is specifically described based on the examples, but the present invention is not limited thereto.

[0061] The following is a summary of various chemicals used in the synthesis of the monomer (1) and polymers (1) to (3). Cyclohexane: manufactured by Kanto Chemical Co., Ltd. Pyrrolidine: manufactured by Kanto Chemical Co., Ltd. Divinylbenzene: manufactured by Sigma-Aldrich 1.6 M n-butyl lithium hexane solution: manufactured by Kanto Chemical Co., Ltd. Isopropyl alcohol: manufactured by Kanto Chemical Co., Ltd. Styrene: Made by Kanto Chemical Co., Ltd. Butadiene: Made by Takachiho Chemical Co., Ltd. Tetramethylethylenediamine: manufactured by Kanto Chemical Co., Ltd. Modifier: 3-(N,N-dimethylaminopropyl)trimethoxysilane manufactured by Azmax 2,6-tert-Butyl-p-cresol: manufactured by Ouchi Shinko Chemical Industry Co., Ltd. Methanol: Made by Kanto Chemical Co., Ltd.

[0062] (Synthesis of Monomer (1)) In a 100 ml container fully purged with nitrogen, 50 ml of cyclohexane, 4.1 ml of pyrrolidine and 8.9 ml of divinylbenzene were added, and 0.7 ml of 1.6 M n-butyllithium hexane solution was added at 0°C and stirred. After 1 hour, isopropanol was added to stop the reaction, and extraction and purification were performed to obtain monomer (1).

[0063] (Synthesis of polymer (1)) In a 1000 ml pressure vessel fully substituted with nitrogen, 600 ml of cyclohexane, 12.6 ml of styrene, 71.0 ml of butadiene, 0.06 g of monomer (1), and 0.11 ml of tetramethylethylenediamine were added, and 0.2 ml of 1.6 M n-butyl lithium hexane solution was added at 40°C and stirred. After 3 hours, 0.5 ml of a modifier was added and stirred. After 1 hour, 3 ml of isopropanol was added to stop the polymerization. 1 g of 2,6-tert-butyl-p-cresol was added to the reaction solution, and a secondary precipitation treatment was performed with methanol. The polymer (1) was obtained by heating and drying.

[0064] (Synthesis of polymer (2)) The amount of the monomer (1) was set to 0.17 g, and a polymer (2) was obtained in the same manner as in the above polymer (1).

[0065] (Synthesis of polymer (3)) The amount of the monomer (1) was set to 0.29 g, and a polymer (3) was obtained in the same manner as in the above polymer (1).

[0066] Below is a summary of the various chemicals used in each formulation. BR: BR150B manufactured by Ube Industries, Ltd. Polymers (1) to (3): synthesized by the above method Silicon dioxide: ULTRASIL VN3 (N 2 SA: 175m 2 / g) Silane coupling agent 1: Si69 manufactured by EVONIK Degussa Silane coupling agent 2: NXT-Z45 manufactured by Momentive Oil: Diana Process AH-24 manufactured by Idemitsu Kosan Co., Ltd. Stearic acid: Tsubaki stearic acid manufactured by NOF Corporation Antioxidant: NOCRAC 6C (N-(1,3-dimethylbutyl)-N'-phenyl-p-phenylenediamine) manufactured by Ouchi Shinko Chemical Industry Co., Ltd. Wax: SUNNOC WAX manufactured by Ouchi Shinko Chemical Co., Ltd. Sulfur: Powdered sulfur manufactured by Tsurumi Chemical Co., Ltd. Vulcanization accelerator 1: NOCCELLER CZ (N-cyclohexyl-2-benzothiazolylsulfenamide) manufactured by Ouchi Shinko Chemical Industry Co., Ltd. Vulcanization accelerator 2: NOCCELLER D (N,N'-diphenylguanidine) manufactured by Ouchi Shinko Chemical Industry Co., Ltd.

[0067] [Method for evaluating wear resistance of rubber composition] According to the mixing contents shown in Table 1, materials other than sulfur and vulcanization accelerator were kneaded at 150° C. for 5 minutes using a 1.7 L Banbury mixer. Then, sulfur and vulcanization accelerator were added and kneaded at about 80° C. for 3 minutes using an open roll mill to obtain an unvulcanized rubber composition. The obtained unvulcanized rubber composition was press-vulcanized at 170° C. for 12 minutes to obtain a vulcanized rubber composition.

[0068] In addition, the unvulcanized rubber composition obtained was extruded into a tread shape using an extruder having a metal nozzle of a specified shape, and then laminated together with other tire components to form an unvulcanized tire, which was press-vulcanized at 170° C. for 12 minutes to produce a test tire (tire size: 195 / 65R15).

[0069] The vulcanized rubber composition and test tire obtained in the above manner were subjected to the following evaluations.

[0070] 1. SAXS measurement A sheet sample (the above vulcanized rubber composition) swollen in toluene for 12 hours and having a thickness of about 1 mm was mounted on a sample holder and the sample was placed in the q region (q region: 2×10 -3 ~5×10 -3 nm -1 ), the sample was irradiated with X-rays at room temperature. The scattering intensity curve obtained by the measurement at BL03XU and the scattering intensity curve obtained by the measurement at BL20XU were combined using the least square method. The two curves were combined by fixing the scattering intensity curve obtained by BL03XU on the wide angle side and shifting the scattering intensity curve obtained by BL20XU on the small angle side. The scattering intensity curve I was obtained by SAXS measurement. (q) For the obtained scattering intensity curve I (q) , use the above (Formula 2) to perform curve fitting, and use the least square method to calculate the mass fractal dimension D as a fitting parameter.

[0071] (SAXS device) SAXS: SAXS measurement equipment attached to beamlines BL03XU and BL20XU of SPring-8, a large-scale radiation facility owned by the High Brightness Light Science Research Center Foundation (Measurement conditions) X-ray brightness: 5×10 12 photons / s / mrad 2 / mm 2 / 0.1%bw Number of X-ray photons: 2×109 photons / s X-ray energy: 8keV (BL03XU), 23keV (BL20XU) Distance from sample to detector: 3m (BL03XU), 160m (BL20XU) (Detector) 2D detector (image intensifier and CCD camera)

[0072] 2. Actual vehicle test The above test tires were installed on a Japanese FF car, and the groove depth of the tire tread was measured after running 8000 km. The running distance when the tire groove depth decreased by 1 mm was calculated and indexed by the following formula. The larger the index, the better the wear resistance. (Driving distance when the tire groove of each formula is reduced by 1 mm) / (Driving distance when the tire groove of formula 1 is reduced by 1 mm)×100

[0073]

Table 1

[0074] It can be seen from Table 1 that the mass fractal dimension D is highly correlated with the wear resistance. The smaller D is, the better the wear resistance is.

[0075] [Rubber composition] According to the mixing contents shown in Table 2, materials other than sulfur and vulcanization accelerator were kneaded at 150° C. for 5 minutes using a 1.7 L Banbury mixer. Then, sulfur and vulcanization accelerator were added and kneaded at about 80° C. for 3 minutes using an open roll mill to obtain an unvulcanized rubber composition. The obtained unvulcanized rubber composition was press-vulcanized at 170° C. for 12 minutes to obtain a vulcanized rubber composition.

[0076] In addition, the unvulcanized rubber composition obtained was extruded into a tread shape using an extruder equipped with a die of a specified shape, and laminated together with other tire components to form an unvulcanized tire, which was press-vulcanized at 170° C. for 12 minutes to manufacture a test tire (tire size: 195 / 65R15).

[0077] The vulcanized rubber composition and test tire obtained in the above manner were subjected to the following evaluations.

[0078] 1. SAXS measurement A sheet sample (the above vulcanized rubber composition) swollen in toluene for 12 hours and having a thickness of about 1 mm was mounted on a sample holder and the sample was placed in the q region (q region: 2×10 -3 ~5×10-3 nm -1 ), the sample was irradiated with X-rays at room temperature. The scattering intensity curve obtained by the measurement at BL03XU and the scattering intensity curve obtained by the measurement at BL20XU were combined using the least square method. The two curves were combined by fixing the scattering intensity curve obtained by BL03XU on the wide angle side and shifting the scattering intensity curve obtained by BL20XU on the small angle side. The scattering intensity curve I was obtained by SAXS measurement. (q) For the obtained scattering intensity curve I (q) , use the above (Formula 2) to perform curve fitting, and use the least square method to calculate the mass fractal dimension D as a fitting parameter.

[0079] (SAXS device) SAXS: SAXS measurement equipment attached to beamlines BL03XU and BL20XU of SPring-8, a large-scale radiation facility owned by the High Brightness Light Science Research Center Foundation (Measurement conditions) X-ray brightness: 5×10 12 photons / s / mrad 2 / mm 2 / 0.1%bw Number of X-ray photons: 2×10 9 photons / s X-ray energy: 8keV (BL03XU), 23keV (BL20XU) Distance from sample to detector: 3m (BL03XU), 160m (BL20XU) (Detector) 2D detector (image intensifier and CCD camera)

[0080] 2. Actual vehicle test The above test tires were installed on a Japanese FF car, and the groove depth of the tire tread was measured after running 8000 km. The running distance when the tire groove depth decreased by 1 mm was calculated and indexed by the following formula. The larger the index, the better the wear resistance. (Driving distance when the tire groove of each formula is reduced by 1 mm) / (Driving distance when the tire groove of formula 16 is reduced by 1 mm)×100

[0081]

Table 2

[0082] The present invention (1) is a method characterized in that it is a method for evaluating the wear resistance of a rubber composition by X-ray scattering measurement or neutron scattering measurement. The method is based on the scattering intensity curve I obtained by performing X-ray scattering measurement or neutron scattering measurement in the q region represented by the following (Formula 1): (q) A method for evaluating the wear resistance of a rubber composition by using the mass fractal dimension D obtained by curve fitting using the following (Formula 2).

Number 5

Number 6

[0083] The present invention (2) is: the method for evaluating the wear resistance of a rubber composition according to the present invention (1), wherein the q region is 2×10 -3 ~5×10 -3 nm -1 .

[0084] The present invention (3) is a method for evaluating the wear resistance of a rubber composition according to the present invention (1) or (2), wherein the rubber composition is a rubber composition containing a diene rubber and a filler.

[0085] The present invention (4) is a method for evaluating the wear resistance of a rubber composition according to any one of the present inventions (1) to (3), wherein the rubber composition is a rubber composition for a tire.

[0086] The present invention (5) is a rubber composition characterized in that, for a scattering intensity curve I obtained by performing X-ray scattering measurement or neutron scattering measurement in the q region represented by the following (Formula 1), (q) The mass fractal dimension D obtained by curve fitting using the following (Formula 2) is less than 2.30.

Number 7

Number 8

[0087] The present invention (6) is: the rubber composition according to the present invention (5), wherein the mass fractal dimension D is 2.20 or less.

[0088] The present invention (7) is: the rubber composition according to the present invention (5), wherein the mass fractal dimension D is 2.15 or less.

[0089] The present invention (8) is a rubber composition according to any combination of any one of the present inventions (5) to (7), wherein the q region is 2×10 -3 ~5×10 -3 nm -1 .

[0090] The present invention (9) is a rubber composition according to any combination of any one of the present inventions (5) to (8), comprising a rubber component containing a diene rubber and a filler.

[0091] The present invention (10) is: according to the rubber composition described in the present invention (9), wherein the diene rubber contains styrene butadiene rubber, and the content of the styrene butadiene rubber in 100% by mass of the rubber component is 40 to 80% by mass.

[0092] The present invention (11) is the rubber composition according to the present invention (9) or (10), further comprising a mercapto-based silane coupling agent.

[0093] The present invention (12) is a rubber composition according to any combination of any one of the present inventions (5) to (11), wherein the rubber composition is a rubber composition for a tire.

Claims

1. A method for evaluating the wear resistance of a rubber composition, characterized in that: This is a method for evaluating the wear resistance of a rubber composition by X-ray scattering measurement or neutron scattering measurement. The method is a method for evaluating the wear resistance of a rubber composition based on a mass fractal dimension D, wherein the mass fractal dimension D is a scattering intensity curve I obtained by performing an X-ray scattering measurement or a neutron scattering measurement in a q region represented by the following (Formula 1): (q) , obtained by curve fitting using the following (Formula 2), 【Number 1】 (Formula 1) θ: scattering angle, λ: wavelength of X-ray or neutron ray, 【Number 2】 (Formula 2) I (q) ∝q -D D: Quality fractal dimension.

2. The method for evaluating the wear resistance of a rubber composition according to claim 1, wherein: The q area is 2×10 -3 ~5×10 -3 nm -1 .

3. The method for evaluating the wear resistance of a rubber composition according to claim 1, wherein: The rubber composition is a rubber composition containing a diene rubber and a filler.

4. The method for evaluating the wear resistance of a rubber composition according to claim 1, wherein: The rubber composition is a rubber composition for tires.

5. A rubber composition, characterized in that: The scattering intensity curve I obtained by performing X-ray scattering measurement or neutron scattering measurement in the q region represented by the following (Formula 1) is (q) The mass fractal dimension D obtained by curve fitting using the following (Formula 2) is less than 2.

30. 【Number 3】 (Formula 1) θ: scattering angle, λ: wavelength of X-ray or neutron ray, 【Number 4】 (Formula 2) I (q) ∝q -D D: Quality fractal dimension.

6. The rubber composition according to claim 5, wherein The mass fractal dimension D is less than 2.

20.

7. The rubber composition according to claim 5, wherein The mass fractal dimension D is less than 2.

15.

8. The rubber composition according to claim 5, wherein The q area is 2×10 -3 ~5×10 -3 nm -1 .

9. The rubber composition according to claim 5, wherein: It contains a rubber component including a diene rubber and a filler.

10. The rubber composition according to claim 9, wherein The diene rubber contains styrene butadiene rubber, and the content of the styrene butadiene rubber in 100% by mass of the rubber component is 40 to 80% by mass.

11. The rubber composition according to claim 9, wherein It further contains a mercapto-based silane coupling agent.

12. The rubber composition according to claim 5, wherein This is a rubber composition for tires.

13. The rubber composition according to claim 9, wherein The content of the filler is 30 to 120 parts by mass based on 100 parts by mass of the rubber component.

14. The rubber composition according to claim 13, wherein The filler is silicon dioxide.

15. The rubber composition according to claim 5, wherein The mass fractal dimension D is greater than 1.

Citation Information

Patent Citations

  • Tire abrasion lifetime prediction method

    JP2005308447A

  • Rubber composition and tire using the same

    JP2010116554A